A magnetic fluid material for conductor anti-icing and preparation method thereof
Manganese-zeb ferrite nanoparticles were prepared and modified by hydrothermal method, and the problems of iron loss effect and corona in the application of transmission conductors were solved, and low iron loss effect and magnetofluid materials with excellent anti-ice or frost performance were achieved.
Patent Information
- Application Number
- CN202410822296.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-24
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-06-24
AI Technical Summary
When used in transmission conductors, existing magnetofluid materials have problems such as iron loss effect and aggravation of corona, and poor heat source control may lead to line heating and safety hazards.
Manganese zinc ferrite nanoparticles were prepared by hydrothermal method. Nanoparticles with particle sizes of 100-150 nm were prepared by adjusting the material ratio and process parameters, and modified by oleic acid and fluorosilane to form a magnetofluid material with low Curie temperature and small iron loss effect.
It achieves low iron loss effect and excellent anti-ice or frost performance, reduces the corona risk of transmission conductors, and avoids safety hazards of line heating through improved thermal management.
Smart Images

Figure CN118942830B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of anti-icing materials, and in particular relates to a magnetic fluid material for anti-icing of conductors and a preparation method thereof. Background Art
[0002] Transmission line icing seriously threatens the safe operation of power systems, and my country is one of the countries with the most serious icing disasters on power lines. At present, the commonly used methods for preventing and controlling icing of power lines include mechanical methods, natural passive methods, wire surface modification methods and thermal methods. Among them, the mechanical method can only reduce the disaster to a certain extent, but cannot prevent it. The natural passive method will cause line accidents of wire jumping due to uneven or different periods of deicing. The surface modification method has no effect on ice formed by frost. Thermal deicing uses additional heat sources or the heat of the wire itself to prevent ice and snow from accumulating on the wire or to melt the accumulated ice and snow. Studies have found that magnetic fluid (also known as magnetic liquid), a new functional material, has both the fluidity of liquid and the magnetism of solid magnetic materials, and can theoretically be used to prevent wire icing. However, for transmission lines, since there is always an alternating current, there is always a strong magnetic field strength. If the magnetic fluid always exists on the surface of the line in a protruding state during line operation, it may become a defect that causes the corona of the line to intensify. In addition, if the heating of magnetic materials is not well controlled, it will become a heat source, causing the line to heat up and cause safety hazards.
[0003] At present, there are relatively few reports on the use of magnetic fluid materials in the field of anti-icing. There are patents for the use of magnetic fluid materials in aviation anti-icing, such as CN110774709A and CN111806701A. Taking CN111806701A (20201023) as an example, the patent discloses a magnetically sensitive porous anti-icing composite material. F3O4 nanoparticles with a commercial particle size of 800nm, polydimethylsiloxane, toluene and silicone oil are mixed and cured, and applied to the anodized pores to obtain a better anti-icing effect. However, the iron loss effect of this material is unknown, and there are hidden dangers when it is applied to power transmission lines.
[0004] In summary, it is necessary to propose new methods and materials to supplement the deficiencies of existing technologies. Summary of the invention
[0005] In view of this, the object of the present invention is to provide a magnetic fluid material and a preparation method for conductor anti-icing, and the specific technical scheme is as follows.
[0006] A manganese zinc ferrite nanoparticle, the molecular formula of the manganese zinc ferrite nanoparticle is (Mn x Zn y)Fe2O4, X=0.1-1, Y=0.1-1; comprising the following materials in parts by weight: 10-40 parts of ferric nitrate, 1-10 parts of manganese nitrate and 1-15 parts of zinc nitrate.
[0007] Furthermore, X=0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or 1; Y=0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or 1.
[0008] Furthermore, the manganese zinc ferrite nanoparticles are made of the following materials in parts by weight: 30-40 parts of iron nitrate, 5-10 parts of manganese nitrate and 10-15 parts of zinc nitrate.
[0009] Preferably, the manganese zinc ferrite nanoparticles are made of the following materials in parts by weight: 40 parts of iron nitrate, 10 parts of manganese nitrate and 10 parts of zinc nitrate.
[0010] As a preferred embodiment, the molecular formula of the manganese zinc ferrite nanoparticles is (Mn x Zn y )Fe2O4, X=0.5, Y=0.5.
[0011] Furthermore, the particle size of the manganese zinc ferrite nanoparticles is in the range of about 100-200 nm.
[0012] Preferably, the particle size of the manganese zinc ferrite nanoparticles is in the range of about 100-150 nm.
[0013] Furthermore, the particle size range of the manganese zinc ferrite nanoparticles includes 100-110nm, 110-120nm, 120-130nm, 130-140nm or 140-150nm.
[0014] The preparation method of the above-mentioned manganese zinc ferrite nanoparticles is a hydrothermal method, and the specific steps are as follows:
[0015] S01: Add the following materials in parts by weight into pure water and stir: 10-40 parts of ferric nitrate, 1-10 parts of manganese nitrate and 1-15 parts of zinc nitrate, and adjust the pH value of the reaction solution to alkaline;
[0016] S02: adding the reaction solution into a reaction kettle for hydrothermal reaction at a temperature of 100 to 300° C. for 6 to 48 hours;
[0017] S03: centrifuging the product after the reaction (optionally washing with ethanol), then drying, grinding and annealing. The annealing process is heating to 600-1200° C. at a heating rate of 3-10° C. / min, keeping the temperature for 4-24 hours, and cooling to room temperature to obtain a crude product of manganese zinc ferrite nanoparticles;
[0018] S04: adding the crude manganese zinc ferrite nanoparticles to 5%-25% oleic acid and / or 3%-20% fluorosilane ethanol for modification to obtain the modified manganese zinc ferrite nanoparticles.
[0019] Furthermore, in S01, the pH value of the reaction solution is adjusted to be in the range of 9-11.
[0020] Furthermore, the reaction solution in S02 is subjected to hydrothermal reaction in a reactor at a temperature of 120-180° C. for 12-18 hours.
[0021] Furthermore, the annealing process in S03 is to heat to 900-1000° C. at a heating rate of 5-10° C. / min, keep the temperature for 12-24 hours, and cool to room temperature.
[0022] Furthermore, in S04, the crude manganese zinc ferrite nanoparticles are added to methanol for ultrasound, and then 5%-25% oleic acid and / or 3%-20% fluorosilane ethanol are added for reaction, and the product is further heated to remove the unreacted solvent and then cleaned. After drying, it is adsorbed and collected by magnetic material (to prove that the prepared nanoparticles have magnetism) to obtain the modified manganese zinc ferrite nanoparticles.
[0023] As a preferred embodiment, in S04, the crude manganese zinc ferrite nanoparticles are modified with 5%-25% oleic acid and 3%-20% fluorosilane.
[0024] Modification with oleic acid or fluorosilane can make the surface of manganese zinc ferrite nanoparticles have organic active groups or hydrophobicity, so that they can be better combined with oil-based solvents such as silicone oil to form a uniform magnetic fluid.
[0025] The above-mentioned manganese-zinc ferrite nanoparticles are used in the preparation of anti-icing magnetic fluid coating or anti-frost magnetic fluid coating for power transmission lines.
[0026] Furthermore, the manganese zinc ferrite nanoparticles are uniformly mixed with an oil-based solvent such as silicone oil, and then ultrasonically treated to prepare a magnetic fluid coating.
[0027] Furthermore, the magnetic fluid coating can be filled into the porous surface structure of the transmission wire by applying a certain magnetic field through a magnet.
[0028] Beneficial technical effects
[0029] The present invention adopts a hydrothermal method to prepare a manganese zinc ferrite nanoparticle with a particle size of about 100nm and a tetragonal crystal structure. The manganese zinc ferrite nanoparticle has a low Curie temperature and a very small iron loss effect, and is used for the preparation of anti-icing and anti-frost materials for power transmission lines.
[0030] Secondly, the present invention modifies the prepared manganese zinc ferrite nanoparticles with oleic acid, fluorosilane or a combination of oleic acid and fluorosilane, so that the surface of the manganese zinc ferrite nanoparticles has active groups or exhibits hydrophobic properties. Subsequently, the nanoparticles can be better combined with oil-based solvents such as silicone oil to form a uniform magnetic fluid material (or magnetic fluid coating), which is applied to a super-hydrophobic oxidation pore structure that is resistant to low temperature and high humidity, so that the transmission wire has excellent anti-icing or anti-frost performance.
[0031] Finally, the hydrothermal preparation method adopted in the present invention is relatively simple to operate, has low equipment requirements, and has controllable overall costs, and is suitable for large-scale industrial promotion. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings required for use in the embodiments or the prior art descriptions are briefly introduced below. In all the drawings, similar elements or parts are generally identified by similar reference numerals. In the drawings, each element or part is not necessarily drawn according to the actual scale. Obviously, the drawings described below are some embodiments of the present invention. For those of ordinary skill in the art, other drawings can also be obtained based on these drawings without paying creative labor.
[0033] Figure 1 Manganese zinc ferrite nanoparticles prepared in one embodiment of the present invention;
[0034] Figure 2 This is an electron microscope image of a material obtained by reacting in a water bath at 60° C. for 12 hours in one embodiment of the present invention;
[0035] Figure 3 This is an electron microscope image of a material obtained by reacting in a water bath at 80° C. for 12 hours in one embodiment of the present invention;
[0036] Figure 4 This is an electron microscope image of a material obtained by reacting in a water bath at 120° C. for 12 hours in one embodiment of the present invention;
[0037] Figure 5 This is an electron microscope image of a material obtained by reacting at 180° C. in a water bath for 12 hours in one embodiment of the present invention;
[0038] Figure 6 This is an oxidation pore structure resistant to low temperature and high humidity frosting prepared in one embodiment of the present invention (scale bar is 1 μm);
[0039] Figure 7 The Curie temperature of the manganese zinc ferrite nanoparticles prepared in one embodiment of the present invention;
[0040] Figure 8This is a thermogravimetric test diagram of manganese zinc ferrite nanoparticles prepared in one embodiment of the present invention;
[0041] FIG9 is a test of the anti-frost and anti-icing performance of manganese-zinc ferrite nanoparticles in one embodiment of the present invention (A is an experimental sample, and B is a control sample);
[0042] Fig.10 This is the iron loss test result of the manganese zinc ferrite nanoparticles in one of the embodiments of the present invention. DETAILED DESCRIPTION
[0043] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0044] Herein "and / or" includes any and all combinations of one or more of the associated listed items.
[0045] Herein, "plurality" means two or more than two, ie, it includes two, three, four, five, etc.
[0046] It should be noted that, in this article, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, an element defined by the sentence "comprises a ..." does not exclude the existence of other identical elements in the process, method, article or device including the element.
[0047] As used in this specification, the term "about" typically means + / - 5% of the stated value, more typically + / - 4% of the stated value, more typically + / - 3% of the stated value, more typically + / - 2% of the stated value, even more typically + / - 1% of the stated value, and even more typically + / - 0.5% of the stated value.
[0048] In this specification, some embodiments may be disclosed in a format of being within a certain range. It should be understood that such description of "being within a certain range" is only for convenience and brevity, and should not be interpreted as a rigid limitation on the disclosed range. Therefore, the description of the range should be considered to have specifically disclosed all possible sub-ranges and independent numerical values within this range. For example, the range The description of should be considered to have specifically disclosed sub-ranges such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6 etc., as well as individual numbers within this range, for example, 1, 2, 3, 4, 5, and 6. The above rules apply regardless of the breadth of the range.
[0049] Example 1
[0050] This embodiment provides an example of a method for preparing manganese zinc ferrite nanoparticles.
[0051] Preparation method:
[0052] S01: Add the following materials in parts by weight into pure water and stir: 40 parts of ferric nitrate, 10 parts of manganese nitrate and 10 parts of zinc nitrate; adjust the pH value of the reaction solution to 10.
[0053] S02: Add the reaction solution into a reactor and perform hydrothermal reaction at 180° C. for 12 h.
[0054] S03: The solution after the reaction is completed is centrifuged and washed with ethanol for 3 times, followed by drying, grinding and annealing to obtain crude manganese zinc ferrite nanoparticles; wherein the centrifugation operation is centrifugation at 8500rpm for 5 minutes; the annealing operation is placing the powder in a crucible, heating it to 900-1000℃ in a muffle furnace at a heating rate of 5℃ / min, keeping it warm for 12-24h, and cooling it to room temperature with the furnace.
[0055] S04: The crude manganese zinc ferrite nanoparticles are added to methanol for ultrasonication, and 5%-25% oleic acid (OA) is further added, and the methanol is removed by heating at 60-90°C, and the excess unreacted oleic acid is filtered out, and the nanoparticles are cleaned with methanol or ethanol, and adsorbed and collected by magnet to obtain oleic acid-modified manganese zinc ferrite nanoparticles. Alternatively, the crude manganese zinc ferrite nanoparticles are added to methanol for ultrasonication, and 3%-20% fluorosilane (FAS) ethanol solution is further added, and the nanoparticles are cleaned after heating at 60-90°C to remove ethanol, and the nanoparticles are adsorbed and collected by magnet to obtain fluorosilane-modified manganese zinc ferrite nanoparticles. Alternatively, the crude manganese zinc ferrite nanoparticles are added to methanol for ultrasonication, and 5%-25% oleic acid (OA) and 3%-20% fluorosilane (FAS) are further added for co-modification, and the reaction is washed after completion, and finally OA+FAS co-modified manganese zinc ferrite nanoparticles are collected.
[0056] It can be understood that the modification with oleic acid makes the surface of manganese zinc ferrite nanoparticles have organic active groups; the modification with fluorosilane makes the surface of manganese zinc ferrite nanoparticles have -CF groups, so that they have a certain hydrophobicity, further improving the anti-icing and anti-frost performance.
[0057] Control 1: No annealing: S01-S02.
[0058] S01: Add the following materials in parts by weight into pure water and stir: 40 parts of ferric nitrate, 10 parts of manganese nitrate and 10 parts of zinc nitrate; adjust the pH value of the reaction solution to 10.
[0059] S02: Add the reaction solution into a reactor and perform hydrothermal reaction at 180° C. for 12 hours. Centrifuge the solution after the reaction and wash it with ethanol for 3 times, then dry and grind it to obtain crude manganese zinc ferrite nanoparticles; wherein the centrifugation operation is centrifugation at 8500 rpm for 5 minutes.
[0060] Control 2: No modification after annealing: S01-S03.
[0061] S01: Add the following materials in parts by weight into pure water and stir: 40 parts of ferric nitrate, 10 parts of manganese nitrate and 10 parts of zinc nitrate; adjust the pH value of the reaction solution to 10.
[0062] S02: Add the reaction solution into a reactor and perform hydrothermal reaction at 180° C. for 12 h.
[0063] S03: The solution after the reaction is completed is centrifuged and washed with ethanol for 3 times, followed by drying, grinding and annealing to obtain crude manganese zinc ferrite nanoparticles; wherein the centrifugation operation is centrifugation at 8500rpm for 5 minutes; the annealing operation is placing the powder in a crucible, heating it to 900-1000℃ in a muffle furnace at a heating rate of 5℃ / min, keeping it warm for 12-24h, and cooling it to room temperature with the furnace.
[0064] The molecular formula of the manganese zinc ferrite nanoparticles prepared in this example is (Mn 0.5 Zn 0.5 )Fe2O4, SEM image is shown in Figure 1 (A is unannealed nanoparticles, the scale bar is 2μm; B is annealed unmodified nanoparticles, the scale bar is 100nm; C is annealed + OA modified nanoparticles, the scale bar is 200nm; D is annealed + OA + FAS co-modified nanoparticles, the scale bar is 200nm), among which, the manganese zinc ferrite nanoparticles modified with OA or OA + FAS have a particle size range of about 100-150nm, and the crystal morphology is complete, basically square.
[0065] Example 2
[0066] This embodiment provides another example of a preparation method.
[0067] (1) Different crystal morphologies can be obtained by adjusting the hydrothermal reaction parameters and material ratio.
[0068] Table 1
[0069]
[0070]
[0071] Example 3
[0072] This embodiment prepares an oxidized pore structure for accommodating a manganese-zinc ferrite magnetic fluid material.
[0073] Method and steps: After the aluminum plate is pre-treated (acid washing, alkali washing and water washing), it is anodized for 20 minutes in a room temperature phosphoric acid electrolyte (3 mol / L) in a voltage-stabilizing mode with a voltage of 120 V, and the oxidized plate is cleaned and dried. The oxidized plate is immersed in a fluorosilane ethanol solution (3 wt.%) for 4 hours, and dried and cured at 120° C. to obtain an oxidized pore structure simulating a transmission line.
[0074] See Figure 6 It is obvious from the figure that the pore size of the oxidized pore structure is about 250 to 350 nm, so the manganese zinc ferrite nanoparticles prepared in Example 1 can completely enter the pores. It can be understood that the modified manganese zinc ferrite nanoparticles are evenly mixed with oil-based solvents such as silicone oil to prepare a magnetic fluid, which is further filled into the oxidized pore structure for anti-icing or anti-frost.
[0075] Example 4
[0076] This example provides performance verification of manganese zinc ferrite nanoparticles.
[0077] 4.1 Curie temperature
[0078] Method and steps: The SQUID-VSM magnetic measurement system of Quantum Design Company in the United States is used. The system is based on quantum superconducting interference device detection technology. By applying a DC or AC magnetic field to the magnetic material, the DC (AC) magnetization intensity of the sample to be tested changes with temperature (field strength) curves, that is, the measurement of MH and MT curves, is obtained. The MT curve is fitted with a straight line, and the temperature point with the largest slope is the Curie temperature point. The specific steps are as follows.
[0079] (1) Weigh the mass of magnetic powder.
[0080] (2) Load the sample into the instrument sample rod and place the sample rod into the sample cavity.
[0081] (3) Clean the cavity with helium (the program defaults to cleaning three times) and then evacuate it.
[0082] (4) Set the temperature (100K-400K) and magnetic field (1.5T), and determine the sample position by scanning the sample's "signal-position" curve.
[0083] (5) By applying a DC or AC magnetic field to the magnetic powder, the DC (AC) magnetization intensity of the sample to be tested changes with temperature (field strength) curve, that is, the MT curve measurement. The MT curve is fitted with a straight line, and the temperature point with the largest slope is the Curie temperature point.
[0084] Example 1 OA+FAS co-modified manganese zinc ferrite nanoparticles (Mn 0.5 Zn 0.5 )Fe2O4) samples were tested by MT, such as Figure 7 As shown, the Curie temperature is about 279.84K, reaching a low temperature state (around 6°C).
[0085] 4.2 Thermogravimetric test
[0086] Method and steps: Thermogravimetric analyzer (TGA) is used for detection. Under program temperature control (0°C to 1200°C, heating for 1 hour), the relationship between the mass of magnetic powder and temperature (or time) is measured, and the endothermic and exothermic processes in the process are measured.
[0087] Example 1 Manganese zinc ferrite nanoparticles (Mn 0.5 Zn 0.5 )Fe2O4) samples were subjected to thermogravimetric testing. Figure 8 As shown, it can remain stable at about 900°C for about 1 hour.
[0088] Example 5
[0089] This embodiment provides the anti-icing and anti-frost performance of manganese zinc ferrite nanoparticles.
[0090] Method and steps: Using semiconductor refrigeration platform LTD1-350, the samples were placed on the semiconductor refrigeration platform for frosting experiment at -8°C. The samples were placed on a magnet with a magnetic field of 2600GS. The black part was the sample coated with OA+FAS co-modified manganese zinc ferrite nanoparticles (magnetic fluid) (experimental sample), and the white part was the sample not coated (control sample). The experimental samples and control samples were placed in a high humidity and low temperature environment (-8°C, humidity 99%).
[0091] As shown in Figure 9, at different times, the black part can resist delayed frost formation, while the white part frosts within 20 minutes; in addition, the frost crystals on the rough surface of the experimental sample with magnetic fluid are smaller than those on the white surface, which proves that the magnetic fluid material prepared by the present invention can effectively prevent frost.
[0092] Example 6
[0093] This embodiment provides an iron loss test of manganese zinc ferrite nanoparticles.
[0094] Method and steps: The SQUID-VSM magnetic measurement system from Quantum Design, USA, was used. The specific steps are as follows.
[0095] (1) Weigh the mass of magnetic powder.
[0096] (2) Load the sample into the sample rod and place the sample rod into the sample cavity.
[0097] (3) Clean the chamber with helium (the program defaults to cleaning three times), and then evacuate. (4) Set the temperature (100K-400K) and magnetic field (1.5T), and determine the sample position by scanning the sample's "signal-position" curve.
[0098] (5) By applying a DC or AC magnetic field to the magnetic powder, the DC (AC) magnetization intensity of the sample to be tested is measured as a function of temperature (field strength), i.e., the MH curve. For the MH curve at each temperature, the value of H is calculated when M=0. The larger the absolute value of H, the greater the coercive force, which is more likely to cause heat generation under the alternating magnetic field of power transmission at room temperature, and thus iron loss. Similarly, the smaller the value of H or the closer the curves are to 0, the smaller the coercive force is, the better the paramagnetism is, and the less heat is generated under the alternating magnetic field at room temperature.
[0099] Example 1 OA+FAS co-modified manganese zinc ferrite nanoparticles (Mn 0.5 Zn 0.5 )Fe2O4) was tested by MH, see Fig.10 It can be seen that the coercive forces at temperatures of 260k, 270k, 280k, 290k and 300k are 0.46Oe, 0.085Oe, 0.34Oe, 0.26Oe and 0.025Oe respectively, and the remanence is also very small and close to 0. Therefore, it is determined that the OA+FAS co-modified manganese-zinc ferrite nanoparticles prepared in Example 1 are soft magnetic materials, which will not cause hysteresis loss and heating effect under power transmission, and can be used for anti-icing or anti-frost of power transmission lines.
[0100] The embodiments of the present invention are described above in conjunction with the accompanying drawings, but the present invention is not limited to the above-mentioned specific implementation modes, which are merely illustrative rather than restrictive. Under the guidance of the present invention, ordinary technicians in this field can also make many forms without departing from the scope of protection of the present invention and the claims, all of which are within the protection of the present invention.
Claims
1. A manganese-zinc ferrite nanoparticle with anti-icing and anti-frost properties, characterized in that: The molecular formula of the manganese zinc ferrite nanoparticles is (Mn x Zn y )Fe2O4, X=0.5, Y=0.5; the manganese zinc ferrite nanoparticles have a tetragonal crystal structure and a particle size range of 100-200nm; the preparation method of the manganese zinc ferrite nanoparticles is a hydrothermal method, and the specific steps are as follows: S01: Add the following materials in parts by weight into pure water and stir: 10-40 parts of ferric nitrate, 1-10 parts of manganese nitrate and 1-15 parts of zinc nitrate, and adjust the pH value of the reaction solution to be alkaline; S02: adding the reaction solution into a reactor and subjecting it to a hydrothermal reaction at 180° C. for 12 h; S03: centrifuging the product after the reaction, then drying, grinding and annealing, wherein the annealing process is heating to 600-1200° C. at a heating rate of 3-10° C. / min, keeping the temperature for 4-24 hours, and cooling to room temperature to obtain a crude product of manganese zinc ferrite nanoparticles; S04: adding the crude manganese zinc ferrite nanoparticles to 5%-25% oleic acid and 3%-20% fluorosilane ethanol for modification to obtain the manganese zinc ferrite nanoparticles with anti-icing and anti-frost properties.
2. The manganese zinc ferrite nanoparticles according to claim 1, characterized in that: The manganese zinc ferrite nanoparticles are made of the following materials in parts by weight: 30-40 parts of iron nitrate, 5-10 parts of manganese nitrate and 10-15 parts of zinc nitrate.
3. The manganese zinc ferrite nanoparticles according to claim 1, characterized in that: In S01, the pH value of the reaction solution is adjusted to be in the range of 9-11.
4. The manganese zinc ferrite nanoparticles according to claim 1, characterized in that: The annealing process in S03 is to heat to 900-1000° C. at a heating rate of 5-10° C. / min, keep warm for 12-24 h, and cool to room temperature.
5. The manganese zinc ferrite nanoparticles according to claim 1, characterized in that: In the S04, the crude manganese zinc ferrite nanoparticles are added to methanol for ultrasonic treatment, and then 5%-25% oleic acid and 3%-20% fluorosilane ethanol are added for reaction. The product is further heated to remove the unreacted solvent and then cleaned. After drying, it is adsorbed and collected by magnetic material to obtain the manganese zinc ferrite nanoparticles with anti-icing and anti-frost properties.
6. Use of the manganese-zinc ferrite nanoparticles according to any one of claims 1 to 5 in the preparation of anti-icing magnetic fluid coatings or anti-frost magnetic fluid coatings for power transmission lines.
Citation Information
Patent Citations
Aircraft anti-icing composite material and preparation method thereof
CN110774709A
Implementation method of magneto-sensitive porous lubricating aircraft anti-icing surface
CN111806701A
Method for producing magnetic fluid
CN101136278A
Preparing process of nano Mn-Zn ferrite material
CN1986426A